Healthy and Religious School Climate Strategy as an Effort to Improve Education Quality - Junaidah; Nasir Usman; Suparta Rasyid; Murniati AR; Munawar Fajri (LPPM Undiksha, 2025)
A healthy and religious school climate is an important requirement in education. Lack of integration between school policies, organizational culture, and learning practices impacts the quality of education. This study aims to analyze the strategy for fostering a healthy, religious school climate to improve the quality of education. This research method uses a qualitative method. The research subjects consisted of five participants, including the Principal of a Middle School and four Junior High School Teachers. Data collection techniques included observation, interviews, and documentation by using instruments in the form of observation guidelines, interview guidelines, and documentation sheets. The data obtained were analyzed descriptively. The research results show that a healthy and religious school climate is built through strengthening the school's vision and mission, implementing cleanliness and religious programs, and positive communication between school members. The implications of this study indicate that strengthening a healthy, religious school climate must be systematically integrated into school policies and management as a sustainable strategy to improve the quality of education. Thus, it can be concluded that a healthy and religious school climate is a very crucial factor in improving the quality of education. There is a need to transform the school management perspective so that a healthy, religious school climate becomes a fundamental foundation for improving educators.